Mechanics of circular breathing in wind musicians using cine magnetic resonance imaging techniques. (19th September 2014) - Peng, Tiffany; Phillips, C. Douglas; Dyke, Jonathan P.; Stewart, Michael G.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To investigate the mechanics of circular breathing using cine magnetic resonance imaging (cMRI). Study Design Pilot study. Methods Eight musicians were asked to sustain a note by circular breathing while being studied inside a Siemens Trio 3T magnetic resonance imaging scanner. Subjects were imaged in the midsagittal plane using an innovative T1‐weighted cMRI. Our study population included six professionals and two experienced amateurs (two saxophonists, two trombonists, and four trumpeters). Five predetermined oropharyngeal distances were measured frame by frame. Data were analyzed for displacement and percentage change over time. Oral airway area was measured using automated bounding box techniques. Results All subjects were observed to complete the same series of steps characterized by 1) superior/posterior tongue displacement, 2) inferior/anterior soft palate displacement, 3) anterior tongue/soft palate displacement, 4) superior/posterior soft palate displacement, and 5) return of the tongue to baseline. Posterior oropharyngeal occlusion was demonstrated in bounding box data. Relative occlusion time was significantly longer among experienced amateurs than professionals (P = .01), with a similar trend in absolute occlusion time (P = .08). A trend toward a longer circular breathing cycle time was observed among saxophonists and trumpeters (P = .2), although the difference among trumpeters disappeared when amateurs were excluded. Conclusions Circular breathing has been investigated as therapy for obstructive sleep apnea. This study defines the mechanics of circular breathing for use in training—and potentially in therapy—if proven useful. We demonstrated similar mechanics across subgroups, and increased efficiency among professionals. Our findings demonstrate the feasibility and reliability of cMRI in the dynamic assessment of oropharyngeal motion. Level of Evidence NA Laryngoscope, 125:412–418, 2015